2018
DOI: 10.1016/j.vaccine.2018.05.084
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of on-time vaccination coverage in population subgroups: A record linkage cohort study

Abstract: Reported infant vaccination coverage at age 12 months in Australia is >90%. On-time coverage of the 2-4-6 month schedule and coverage in specific populations is rarely reported. We conducted a population-based cohort study of 1.9 million Australian births, 1996-2012, combining individual birth and perinatal records with immunisation records through probabilistic linkage. We assessed on-time coverage across 13 demographic and perinatal characteristics of diphtheria-tetanus-pertussis vaccines (DTP) defined as va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
5
20
0
Order By: Relevance
“…Regarding the tobacco consumption, those mothers who did not consume any type of tobacco had a lower dropout than the tobacco user. Smoking and vaccination status is consistent with other studies [33,[39][40][41]. A study reported that smoking mothers are likely to start immunization 55.6 days after the schedule [42].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the tobacco consumption, those mothers who did not consume any type of tobacco had a lower dropout than the tobacco user. Smoking and vaccination status is consistent with other studies [33,[39][40][41]. A study reported that smoking mothers are likely to start immunization 55.6 days after the schedule [42].…”
Section: Discussionsupporting
confidence: 89%
“…The introduction of PCV for Aboriginal children in 2001 may have contributed to the ongoing decline in hospitalization rates in the Aboriginal population (though coverage was low at 45–60%) but does not explain the contemporaneous decline in non-Aboriginal children as herd immunity would have been limited prior to the introduction of a national universal PCV program in 2005. When the universal program began, on-time receipt of 7vPCV was 78% for non-Aboriginal children [25]. Pneumococcal serotype or pathogen replacement with non-typeable Haemophilus influenzae following universal introduction of 7vPCV [26] may in part explain the lack of further reduction in OM hospitalization after 2005.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, this limits opportunity to complete the full vaccination schedule and eliminates the possibility of catch-up of missed vaccinations in later childhood [ 25 ]. Delayed and/or incomplete vaccination is more common among Australian Aboriginal children [ 27 ] and in one observational study, two-dose DTPa coverage increased by a further 16% after the upper age limit of rotavirus vaccine administration (from 75% to 91% in Aboriginal infants), whereas two-dose rotavirus vaccine coverage increased by only 3% (from 75% to 78% in Aboriginal infants) [ 28 ]. This suggests that relaxing the upper age restrictions for rotavirus vaccines, as recommended by WHO for countries with high rotavirus burden [ 3 ], could be considered as a strategy for improving vaccine uptake and schedule completion.…”
Section: Discussionmentioning
confidence: 99%